The future of life on Earth - Bright, Michael (Chicago, Ill Raintree, 2012)
Explains how many of the living things on Earth are still to be found and described, as well as things that affect biodiversity and what our world might look like in years to come
A gift from book Africa
The World Around us
1 2 13
NEW_ZTN_GN
Keywords: Exobiology -- Juvenile literature; Life -- Origin -- Juvenile literature